Faith development of the teenager during the Sunday evening worship service - H. P. Jansen (Acta Theologica)
From church conversations with teenagers (born between 1974 and 1994), publications in recent times appeared worldwide and the qualitative investigation in the article is utilized. It seems there are problems in the practice of the faith formation of teenagers in the evening service. The aim of an evening service must always be that God receives all the glory and honour; therefore, the teenager‘s faith may be enriched. The article chooses for the use of the communicative approach to communicate the gospel to teenagers. The article attempts to use the empirical research method to determine which evening worship needs are experienced by teenagers. The article aims to provide the basis of an adjusted practice theory to propose an improved praxis. The article would provide guidelines for all stakeholders that are involved in the planning and execution of the liturgy of the evening worship service. The purpose of this article is to inspire new thinking and doing. The evening service liturgy should be arranged so that every teenager attending the evening service will be aware of the presence of God.